Diagnostic performance of ultrasound in detecting early occult scaphoid fractures: A systematic review - Safrizal Rahman; Azharuddin Azharuddin; Azmi Azmi; Rizki Puji Isnanda; T. Ichsan; Muhammad Azmi (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: The diagnosis of scaphoid fractures is further confounded by the fact that up to 16% may be occult on initial plain radiographs. Clinicians have faced a diagnostic dilemma. It is essential to diagnose quickly and accurately, as delayed or missing diagnoses can result in substantial complications. High-frequency ultrasound has emerged as an option for the early detection of occult scaphoid fractures. There are numerous perks to this modality, such as the capacity to conduct dynamic examinations, the absence of ionizing radiation, the relatively low cost, and the broad availability. Methods: The preferred reporting items for systematic reviews and meta-analyses (PRISMA) was followed for conducting a literature search utilizing PubMed, Cochrane, Science Direct, and Springer Link. The search term “acute occult scaphoid fracture” AND “ultrasound” OR “ultrasonography” was employed. Articles that contained prospective evaluations of the sensitivity and specificity of the use of ultrasonography to diagnose scaphoid fractures were considered. Results: We have obtained 69 studies, after a full-text review, nine studies are suitable for systematic review. The total sample size was around 572 patients with an average age. of 18-41,2. Male patients were higher than female. The article’s quality ranged from moderate to high, based on the MINOR Score. Some studies repeated other imaging modalities (plain radiographs, CT Scan, MRI) to validate the ultrasound results. The mean sensitivity was 77.38% (standard deviation of 22.76) and the mean specificity was 84.74% (standard deviation of 14.71). Conclusion: High-resolution ultrasound performed by experienced operators can achieve sensitivity and specificity comparable to advanced imaging modalities.